2020
DOI: 10.1111/acer.14490
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Interventions to Improve Mental Health and Substance Use Outcomes for Individuals with Prenatal Alcohol Exposure and Fetal Alcohol Spectrum Disorder

Abstract: Individuals with fetal alcohol spectrum disorder (FASD) experience remarkably high rates of mental health and substance use challenges, beginning early in life and extending throughout adulthood. Proactive intervention can help to mitigate some of these negative experiences. Although the literature on FASD intervention is growing, there is currently a lack of consolidated evidence on interventions that may improve mental health and substance use outcomes in this population. Informed by a life course perspectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 91 publications
(145 reference statements)
1
15
0
Order By: Relevance
“…Moreover, most individuals with FASD show no obvious physical signs of impairment ( Andrew, 2011 ), and the “hidden” nature of the disability can further compound the challenges of accurate identification. There is a critical lack of mental health and substance use interventions for individuals with FASD ( Flannigan et al, 2020 ). Furthermore, a lack of recognition of the potential for wellness and resilience among individuals with FASD may create barriers to service access where mental health and substance use treatments are denied because of service providers’ misperceptions about the disability ( Anderson et al, 2019 ).…”
Section: Complexities Of Fetal Alcohol Spectrum Disordermentioning
confidence: 99%
“…Moreover, most individuals with FASD show no obvious physical signs of impairment ( Andrew, 2011 ), and the “hidden” nature of the disability can further compound the challenges of accurate identification. There is a critical lack of mental health and substance use interventions for individuals with FASD ( Flannigan et al, 2020 ). Furthermore, a lack of recognition of the potential for wellness and resilience among individuals with FASD may create barriers to service access where mental health and substance use treatments are denied because of service providers’ misperceptions about the disability ( Anderson et al, 2019 ).…”
Section: Complexities Of Fetal Alcohol Spectrum Disordermentioning
confidence: 99%
“…A recent systematic review of interventions found that the needs of individuals with FASD (and PAE) become more complex in later adolescence, emerging adulthood, and adulthood. This review noted that existing interventions for older individuals were designed with a more responsive approach to mitigate risk and reduce harm (Flannigan et al, 2020). Yet in the larger field of intellectual and developmental disabilities (IDD), over the past four decades, there has been a movement away from this type of “deficits approach,” to a focus on self‐advocacy and the application of strengths‐based approaches to supporting individuals with IDD over the lifespan (Wehmeyer, 2020).…”
Section: A Shift In Perspective To a Focus On Strengths And Quality Of Life In Fasdmentioning
confidence: 99%
“…A discussion of measurable indicators of QOL, aligned with the rights of persons with disabilities, is available and could be used to guide multiple intervention ideas, especially for older individuals with FASD, and their families and service systems (Gómez et al, 2020). This could be a useful resource, as strengths‐based interventions have increasingly been called for in the field of FASD (e.g., Flannigan et al, 2020).…”
Section: A Shift In Perspective To a Focus On Strengths And Quality Of Life In Fasdmentioning
confidence: 99%
“…Importantly, these deficits persist into adulthood, and individuals with FASD can experience lifelong cognitive and physical impairment, psychiatric comorbidity, incarceration, homelessness, and other psychosocial challenges [ 9 , 21 ]. Although the literature on effective treatments for FASD has been growing, at present, very few interventions exist specifically for this population [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%